Impact of Various Otoplasty Techniques on Auricular Deformities and Patient Expectations in Balochistan - Kamal Uddin Khan, Farzana Abdullah, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Otoplasty is a commonly performed aesthetic and reconstructive procedure aimed at correcting auricular deformities, most notably prominent ears. Despite advancements in surgical techniques, there is limited data comparing patient satisfaction and aesthetic outcomes across different otoplasty methods in the regional context of Balochistan, Pakistan. Materials and Methods: This prospective, comparative study was conducted from April 2022 to November 2022 at Bolan Medical Complex, Quetta. A total of 90 patients with congenital or acquired auricular deformities were randomly assigned to undergo one of three otoplasty techniques: Furnas technique (Group A, n=30), Mustardé suture technique (Group B, n=30), or cartilage scoring technique (Group C, n=30). Patient expectations and postoperative satisfaction were assessed using the FACE-Q Ear Module and Visual Analog Scale (VAS). Outcome evaluation included aesthetic assessment by two independent plastic surgeons using standardized pre- and postoperative photography. Statistical analysis involved one-way ANOVA and Pearson correlation. Results: Patients in Group B (Mustardé) reported the highest satisfaction (VAS: 8.7 ± 0.6), followed by Group C (8.1 ± 0.8) and Group A (7.3 ± 1.1), with statistically significant differences (p<0.001). FACE-Q scores also favored Mustardé with enhanced symmetry and contour ratings. Patient expectations were moderately correlated with postoperative satisfaction (r = 0.42, p < 0.01). Complication rates were lowest in Group B. Conclusion: Among the three techniques studied, the Mustardé suture method provided the most favorable aesthetic and satisfaction outcomes for patients undergoing otoplasty in Balochistan. Comprehensive preoperative counseling and technique selection tailored to patient expectations are crucial for optimal results. Keywords: Otoplasty, Mustardé technique, Furnas technique, Auricular deformities, Patient satisfaction, Aesthetic surgery, Balochistan.